Cobertura florestal ou função ecológica: o dilema da restauração na bacia do Rio Sorocaba - Fernandes, Gerson Eli (2016)
The study aimed to evaluate restored areas implemented in the basin of the Sorocaba River and Middle Tiete based on terms of commitments to environmental restoration and conduct adjustment terms. We selected two to three projects in each sub-basin to those with the presence of restoration, certified by the consent of the owner. In each restoration, we evaluated attributes of species diversity and functions, control and management, soil protection and nutrient cycling. The restored areas restoration presented 17 ± 10 species, under the condition established by law, mortality was high, around 40% with an average of 1090 individuals/ha. Croton floribundus, Schinus terebinthifolius, Guazuma ulmifolia, Inga vera, Citharexylum myrianthum, Cordia sellowiana represented 31.7% of species planted and together with Enterolobium contortisiliquum, colubrina Anadenanthera, C. urucurana, Ceiba speciosa, Eugenia uniflora, Lithraea molleoides, Psidium guajava, Triplaris americana, Erythrina speciosa represented 52.8% of the planted individuals. The restoration were in critical situation and, although species richness is according to legal requirements, we observed the concentration on few common and frequent species in general pioneers. Regardless of age, the studied areas did not restore the structural and physical aspects of the forest, and were not efficient in the establishment of ecological processes, highlighting the need to review the procedures adopted in the legal and technical mechanisms of restoration in the region.